On the hydrogen bonding between N-methylformamide and acetone and tetrahydrofuran - Almeida, Glauco G. [UNESP]; Borges, Alexandre [UNESP]; Cordeiro, Joao M. M. [UNESP] (Elsevier B.V., 2014)
Liquid mixtures of N-methylformamide (NMF)-acetone (ACT) and NMF-tetrahydrofuran (THF) 20 mol% NMF have been investigated using Monte Carlo simulations, aiming to obtain new details on the hydrogen bonding donation of the peptide bond in non-aqueous media. There are strong evidences of the H-bonding between NMF and each of the solvents, but the results indicate significant differences between the H-bond interactions in each mixture. THF solvates better the amide than ACT. The NMF-THF H-bonds are more directed and the structure of the solvation shell is much more ordered in the NMF-THF mixture than in the NMF-ACT one. (C) 2014 Elsevier B. V. All rights reserved.
Keywords: Peptide bond; Hydrogen bond; Solvent effects; Conformational stability